Konsumerisme Dalam Tren Brand Fesyen Muslimah Di Jakarta - Qotrunnada, Qotrunnada; Maulana, Moh. Faiz (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2022)
This study aims to look at the consumerism culture that occurs during Muslimah fashion which has now become a trend. The world of fashion, especially Muslim fashion, is growing. Clothing industry agents such as designers and celebrities or influencers are also competing to create Muslimah clothing that can attract consumers' interest, so now we can see Muslimah fashion brands scattered around. Kazami is one of the brands owned by an influencer named Kayla Nadira who has succeeded in becoming a Muslimah fashion brand with quite high enthusiasts. The research method used in this research is descriptive qualitative. With data collection techniques, namely interviews, observation, and also documentation. As well as the theory used in this study is the theory of consumerism by Jean Baudrillard. The results of the study show that there is a pattern of consumptive behavior in the Muslimah fashion phenomenon which has now become a trend. This can be seen from consumers who make purchases not because of the main function of the Muslim clothing itself, but because they are interested in the visual value or display value provided by the products offered through the online market.